Literature Review: The Relationship between Tea Consumption Habits and the Incidence of Anemia in Pregnant Women - Azizatullatifah, Safira; Sarbini, Dwi (Universitas Muhammadiyah Surakarta, 2024)
Introduction: There was an increase in the prevalence of anemia among pregnant women by 11.8% from 2013 to 2018 in Indonesia. The habit of drinking tea is one of the factors associated with anemia in pregnant women due to the presence of tannins in tea that can inhibit the absorption of iron in the body. This literature study aims to examine the relationship between tea drinking habits and the incidence of anemia in pregnant women. Method: Articles were searched through Google Scholar with the keywords